Irregularly branched microvessels as visualized by magnifying endoscopy: a reliable marker for predicting deep submucosal invasion of superficial esophageal squamous cell carcinoma - Yoichiro Ono; Yasuhiro Takaki; Kenshi Yao; Satoshi Ishikawa; Masaki Miyaoka; Yutaka Yano; Takashi Nagahama; Takashi Hisabe; Fumihito Hirai; Toshiharu Ueki; Atsuko Ota; Hiroshi Tanabe; et al. (Endoscopy International Open, 2020)
Background and study aims Magnifying endoscopy with narrow-band imaging (M-NBI) is reported to be useful in diagnosing invasion depth of superficial esophageal squamous cell carcinoma (SCC), but accurate diagnosis of deep submucosal invasion (SM2) has remained difficult. However, we discovered that irregularly branched microvessels observed with M-NBI are detected in SM2 cancers with high prevalence. Thus, this retrospective study aimed to investigate the diagnostic performance of irregularly branched microvessels as visualized by M-NBI for predicting SM2 cancers. Patients and methods Patients with superficial esophageal SCC lesions that were endoscopically or surgically resected at our hospital between September 2005 and December 2014 were included. Endoscopic findings by M-NBI of these lesions were presented to an experienced endoscopist who was unaware of the histopathological diagnosis and who then judged whether irregularly branched microvessels were present. Using the invasion depth according to postoperative histopathological diagnosis as the gold standard, we determined the diagnostic performance of the presence of irregularly branched microvessels as an indicator for SM2 cancers. Results A total of 302 superficial esophageal SCC lesions (228 patients) were included in the analysis. When irregularly branched microvessels were used as an indicator of SM2 cancers, the diagnostic accuracy was 94.0 % (95 % confidence interval [CI]: 91.1–96.1 %), sensitivity was 79.4 % (95 % CI: 66.6–88.4 %), specificity was 95.9 % (95 % CI: 94.3–97.0 %), positive predictive value was 71.1 % (95 % CI: 59.6–79.1 %), and negative predictive value was 97.3 % (95% CI: 95.7–98.5 %). Conclusions Irregularly branched microvessels may be a reliable M-NBI indicator for the diagnosis of cancers with deep submucosal invasion.